Highly stretchable and transparent ionic conducting elastomers - Lei Shi (Nature Portfolio, 2018)
Conductive elastomers are often made of composite materials and realization of high transparency and high elasticity at the same time is therefore hard to achieve. Here the authors use a salt in polymer strategy to fabricate ionic conducting elastomers (ICE), which show good elasticity and transparency and simultaneously high conductivity.